Implementasi Pembelajaran Dalam Jaringan (Daring) Menggunakan Aplikasi Ispring Suite 8 di Taman Kanak-Kanak - Herlina Herlina; Isti Rusdiyani; Cucu Atikah (Universitas Mathla'ul Anwar Banten, 2022)
The weakness of the world of education in Indonesia is the problem of the learning process. In this process students are less motivated to develop thinking skills and skills. For early childhood children at a certain age are not given the opportunity to develop their abilities, both by teachers and parents, it seems that there are still many children who are shy, not independent and not confident.In its implementation, the online learning system during the Covid-19 pandemic encountered several obstacles, including not all students understood internet technology and the need for preparation from the school in such a way. One solution that can be taken by implementing online learning is to use the Ispring suite 8 application which is a tool for creating presentational learning media that can be used in the learning process which includes aspects of audio, visual, audio visual, and audio visual media. various types of evaluations have been carried out. Provided. The Ispring suite 8 application is an application that is run on a computer for use in making learning media either directly, through online learning or a combination of both. the results of this study indicate that the application of online learning using the ispring suite 8 application can increase the creativity of children aged 5-6 years.